A HEI strategy to implement solutions aligned with energy and climate change challenges - Loraine Nazaré; Inês Fernandes; Joaquim Oliveira; Ana Lillebø; Alexandra Queirós (Journal of Sustainability Perspectives, 2023)
The vision of the University of Aveiro (UAveiro) is “to create, share and apply knowledge, involving the whole community through teaching, research, and cooperation with the surrounding environment, in order to make a clear difference for individuals and society”. Framed in the concept of Sustainability and Intergenerational Justice, UAveiro has has act by stimulating behaviours towards sustainability and by implementing solutions aligned with energy and climate change challenges.   Relevant examples are a manual of good environmental sustainability practices, dashboards to monitor our performance, University Footprint Calculator that enables “to think and anticipate realities” towards carbon neutrality without compromising future generations, UAUBike, solutions for sustainability challenges, the greenbuilding’s project.This paper showcases, from different perspectives, the role of UAveiro to contribute to tackle societal challenges arising from the climate crisis and global changes and promote transformative solutions in favour of sustainability, social responsibility and climate action.